Examination of the Informative Part of the Notes to the Financial Statement Amongst Hungarian Companies Engaged in Sports Activities - Kerezsi, Dóra; Dajnoki, Krisztina; Bácsné Bába, Éva; Tarnóczi, Tibor; Fenyves, Veronika (International Journal of Engineering and Management Sciences, 2019)
Currently, the role of sports has intensified and changed; by now, it has become a separate area of interest from an originally civil, exercise-based, private leisure activity. In the case of sports-related economic research, both macro- and microeconomic research can be mentioned. Its economic significance, its contribution to employment, national economic income, and consumer spending is involved in macro-level research, while the examination of the functioning of sports services and organizations, and the characteristics of demand and supply are micro-level research activities. One of the reasons for the development of sports activities was the increase in their economic significance, which created a need for their economic analysis. The necessary information can only be obtained from the two fundamental parts of the annual statements (balance sheet and profit and loss account) if the notes on the account contains the information that contribute to the more comprehensive interpretation of the other parts of the annual statement. In our research, we examine whether the notes on the accounts of companies include the information, which could help obtain necessary financial knowledge concerning the partner companies. For the analyses, we used the notes on the accounts of companies, which have sports activity (Hungarian NACE No. 931) as their main line of business. By means of text mining, we analyse the extent to which the notes on the accounts are in conformity with the Accounting Act.